Men's experience of caring for a family member with cancer: a theory based on data - Larissa de Carli Coppetti; Elisabeta Albertina Nietsche; Maria Denise Schimith; Cremilde Aparecida Trindade Radovanovic; Maria Ribeiro Lacerda; Nara Marilene Oliveira Girardon-Perlini (Universidade de São Paulo, 2024)
Objective: to understand the meaning attributed by men to the experience of caring for their family member with cancer and to develop a substantive theory that represents the experience of men caring for their family member with cancer. Method: this is qualitative research guided by the methodological framework of Grounded Theory and the precepts of Symbolic Interactionism. A form with identification and interview data was used. The analysis followed the substantive and theoretical coding stages. Results: 12 male caregivers of their family member with cancer participated. The constant comparative analysis of the data allowed the creation of a substantive theory "Experiencing the care of a family member with cancer: men as a caregivers" explaining the experience that has as its central category "The love that drives care", representing the symbolic actions and attitudes of men living in the context of illness due to cancer and care Conclusion: the theory allowed us to understand feelings, perceptions, ways of acting and facing the diagnosis, providing care, recognizing difficulties and learning from the situations that arise, making explicit the interactional processes and symbolic elements present and how these influence male caregivers in their actions and attitudes.